Crowds: Das Stadion als Ritual von Intensität - Gumbrecht, Hans-Ulrich (Klostermann, 2020)
Anyone who has ever experienced a football match in a large stadium knows the atmosphere that emanates especially from the grandstands where the real fans are, cheering on their teams. Hans Ulrich Gumbrecht – an avid supporter of Borussia Dortmund and one of the most renowned literary scholars of our time – explores this mood in a special way. In his essay "Crowds" he combines the interior view of the fan with relevant theories of the 20th century. And while "the masses" enjoy a rather dubious reputation in politics and culture (as they are considered to be easily controllable), Gumbrecht discovers a potential for their praise in the fans of Dortmund's "South", one of the world's largest standing room grandstands.